Мета покарання неповнолітніх - Чупринський, Б.; Chuprynskyi, B. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті проведено науковий аналіз проблем визначення мети покарання при призначенні покарання неповнолітнім особам, акцентуються індивідуальні особливості та моральні якості їх характеру. Наголошується на першочерговість виправлення, перевиховання неповнолітнього злочинця, а потім застосування кари, як одного із елементів мети покарання. Аналізується зарубіжний досвід у досягненні мети покарання неповнолітніх злочинців. Підкреслюється важливість проведення загальної та спеціальної превенції до неповнолітніх осіб. The article deals with the scientific analysis of the issues of determining the purpose of imposing punishment on the juveniles. The emphasis is laid on the individual characteristics and moral qualities of the minors. The author argues that the priority should be assigned to the corrective measures, re-educating a juvenile offender and applying punishment, as one of the elements of the juvenile punishment system, only when the preceding measures proved to be insufficient. The study of the foreign experience in achieving the purpose of punishing juvenile offenders contributes to deeper understanding of the issue. The importance is placed on the general and specific preventive measures for the minors since the key purpose of punishing juveniles is to correct their social conduct. This correction should be radical and corresponding to the process of positive changes in the personality of a minor and are aimed at developing his willingness to self-control, obedient behavior. Juvenile offenders punishment is aimed at developing in them critical assessment not only of their own conduct, but also form critical attitude towards committing socially dangerous acts stipulated by the Criminal Code of Ukraine, in general. The study of the concept of juvenile punishment goals proves that formation of a stable, positive social motivation might prevent them from committing new offenses in the future.
The Goals of the Punishment Measures Applied to Juveniles
Keywords: мета покарання; неповнолітні засуджені; злочин; призначення покарання; виправлення; перевиховання; ресоціалізація; ребілітація; правослухняна поведінка; goals of punishment; juvenile convicts; crime; punishment; correction; rehabilitation